2012
DOI: 10.1016/j.actbio.2012.03.019
|View full text |Cite
|
Sign up to set email alerts
|

Development of silk-based scaffolds for tissue engineering of bone from human adipose-derived stem cells

Abstract: Silk fibroin is a potent alternative to other biodegradable biopolymers for bone tissue engineering (TE), because of its tunable architecture and mechanical properties, and demonstrated ability to support bone formation, in vitro and in vivo. In this study, we investigated a range of silk scaffolds for bone TE using human adipose-derived stem cells (hASC), an attractive cell source for engineering autologous bone grafts. Our goal was to understand the effects of scaffold architecture and biomechanics and use t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
184
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 212 publications
(187 citation statements)
references
References 45 publications
2
184
0
1
Order By: Relevance
“…12,13 Thus, ADSCs as seeded cells are widely used for cartilage tissue engineering. [14][15][16] Chondrocyte-related growth factors such as transforming growth factor β, 17 bone morphogenetic proteins, 18 and insulin-like growth factor 19 play a critical role in developing an appropriate microenvironment in cartilage tissue engineering. 20 However, the uncontrolled delivery of these factors may decrease their full reparative potential and have unwanted morphological effects.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 Thus, ADSCs as seeded cells are widely used for cartilage tissue engineering. [14][15][16] Chondrocyte-related growth factors such as transforming growth factor β, 17 bone morphogenetic proteins, 18 and insulin-like growth factor 19 play a critical role in developing an appropriate microenvironment in cartilage tissue engineering. 20 However, the uncontrolled delivery of these factors may decrease their full reparative potential and have unwanted morphological effects.…”
Section: Introductionmentioning
confidence: 99%
“…Most of these approaches have resulted in the in vitro tissue ingrowth with cross-sections of less than a few µm to several mm from the external surface, an incomplete integration with host bone, and only partial bone regeneration in vivo . Therefore, it is clear that the architecture of the scaffolds (pore size, porosity, interconnectivity, and permeability) that affect the transport and diffusion of substances throughout the scaffolds is critical for achieving well-distributed cell proliferation and differentiation 9,10 . Although calcium phosphates have been used in the past for scaffold fabrication, different processes and procedures have often resulted in calcium phosphate scaffolds with varying architectures.…”
Section: Introductionmentioning
confidence: 99%
“…17 It is known that scaffolds for bone tissue regenerations play an important role in influencing the biological responses of cells (including attachment, proliferation, differentiation, etc) and the following new bone tissue formation (scaffolds entirely degraded) in vivo. 18,19 In this study, MWC scaffolds were fabricated using solution casting-particle leaching method. The results revealed that the MWC scaffolds exhibited a well-interconnected macroporous structure, and some micropores were found on the wall of the macropores.…”
Section: Discussionmentioning
confidence: 99%